Evaluación de compuestos volátiles de Bacillus spp. frente a fitopatógenos en uvilla - Domínguez Olmedo, Emily Camila (2024)
The production of uvilla (Physalis peruviana L.) has had an impact on the socio-economic growth of the Ecuadorian agricultural sector; however, producers face losses during the post-harvest period due to the action of phytopathogens. Control strategies include the use of synthetic fungicides, resulting in serious environmental damage. Globally, biocontrollers are used, which are living organisms employed to reduce the action of phytopathogens. Therefore, this study evaluated the capacity of volatile organic compounds (VOCs) produced by Bacillus spp. against the phytopathogenic fungi Botrytis cinerea and Fusarium oxysporum in post-harvest uvilla fruits. Eight soil samples were collected from fields in the provinces of Pichincha and Santo Domingo de los Tsáchilas. Colonies with characteristics similar to Bacillus bacteria were isolated, molecularly identified using PCR, and their sequencing results were compared in the NCBI and EZ Bio Cloud databases. The effect of VOCs on phytopathogens was evaluated in vitro using the double plate technique. Four strains (EDB-09, EDB-08, and EDB-10) were isolated and identified as Bacillus sp., except for EDBS-02, identified as Bacillus siamensis. Regarding the effect of VOCs, a moderate to high percentage of growth inhibition (PGI) was recorded in the phytopathogens B. cinerea and F. oxysporum. In conclusion, the VOCs produced by the strains evaluated in vitro constitute an inhibitory mechanism to halt the development of uvilla pathogens.